STUDENTS' DIFFICULTIES IN WRITING ENGLISH TH2 8 MIFTAHUL ULUM 2 PUNGGUR - Mas'udi (Cahaya Ilmu Bangsa Institute, 2024)
Mas'udi 2023 Analysis of Students' Ability and Examination in Descriptive Writing (Studies in Grade II MTs MIFTAHUL ULUM 2 PUNGGUR). Faculty of Teacher Training and Education, University of UNU KALBAR. Supervised by Miss Alvina Yolanda and mister nizar. This study aims to determine the abilities and difficulties of MTs MIFTAHUL ULUM 2 PUNGGUR students in writing descriptive texts. The method used in this research is descriptive quantitative. The researcher used a written test as the instrument. The population of this study were students of class VIII MTs MIFTAHUL ULUM 2 PUNGGUR for the 2022/2023 academic year. The sample is class VIII which consists of 12 students selected by using purposive sampling. The finding indicated that the students ability in writing descriptive text was classified into very poor. The students writing ability in content categories was 2.63. It was classified very poor. The students writing in organization was 2.09. It was classified very poor. The students writing in vocabulary was 2,93. It was classified very poor. The students writing in grammar was 1,75. It was classified very poor. And the students writing in mechanic was 2,33. It was classified very poor. While the students difficulties in writing was Language features of descriptive text consist of describing object in detail, lack of vocabulary and grammar mastery so majority of the students was difficult to create the sentences and write correct spelling words. From the result, the researcher is able to conclude that students have not deep understanding in writing of descriptive text.